Volleyball - an ethnographic drama - Blackledge, Adrian 1959- (Multilingual Matters, 2021)
In this book research in process and research findings are represented in a play script which brings vividly to life both ethnographic research methods and communication in the world of sport. This highly original book brings innovation and imagination to the representation of language in social life